2018
DOI: 10.1101/381541
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Triple A patient cells suffering from mitotic defects fail to localize PGRMC1 to mitotic kinetochore fibers

Abstract: Abbreviations: ALADIN, alacrima-achalasia-adrenal insufficiency neurologic disorder; CYP, cytochrome P450; ER, endoplasmic reticulum; GFP, green fluorescent protein; NADPH, Nicotinamide adenine dinucleotide phosphate; NUP, nucleoporin; PGRMC1 and 2, progesterone receptor membrane component 1 and 2 Investigating cell division in human adrenal cells we show that proliferation is decreased upon overexpression of ALADIN, PGRMC1 or PGRMC2.• In immunofluorescence experiments using human adrenal cells and triple A pa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…We show that changes in posttranslational modification of PGRMC1 are involved in the maintenance of genomic integrity. Future research should examine whether this involves previously reported PGRMC1 involvement with G0/G1 checkpoint and/or spindle association (Cahill et al, 2016a;Griffin et al, 2014;Juhlen et al, 2018;Luciano and Peluso, 2016;Terzaghi et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We show that changes in posttranslational modification of PGRMC1 are involved in the maintenance of genomic integrity. Future research should examine whether this involves previously reported PGRMC1 involvement with G0/G1 checkpoint and/or spindle association (Cahill et al, 2016a;Griffin et al, 2014;Juhlen et al, 2018;Luciano and Peluso, 2016;Terzaghi et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…Progesterone (P4) Receptor Membrane Components 1 (PGRMC1) is a cytochrome b5 (cytb5) protein and a member of the membrane-associated P4 receptor (MAPR) family with a plethora of cellular functions. These include some cytb5-typical functions that predate or are potentially ancient in eukaryotes (regulation of heme synthesis (Piel et al, 2016), cyP450 (cytochrome P450) interactions (Oda et al, 2011;Ryu et al, 2017;Szczesna-Skorupa and Kemper, 2011), sterol metabolism (Cahill and Medlock, 2017;Hughes et al, 2007;Mallory et al, 2005)), some that evidently arose in eukaryotes (membrane trafficking (reviewed by: Cahill et al, 2016a;Mifsud and Bateman, 2002), cell cycle regulation at the G0/G1 checkpoint (Cahill et al, 2016a;Griffin et al, 2014;, mitotic/meiotic spindle association (Juhlen et al, 2018;Luciano and Peluso, 2016;Terzaghi et al, 2016)), and clearly specialized metazoan functions including e.g., fertility, embryogenic axon guidance, and membrane trafficking associated with synaptic plasticity (reviewed by: Cahill et al, 2016a;Rohe et al, 2009). CyP450-interactions (Ryu et al, 2017) conspicuously feature PGRMC1 regulation of the most conserved eukaryotic cyP450 (lanosterol 14-alpha demethylase, CYP51A) to modify the first sterol (lanosterol) from yeast to mammals (Cahill, 2007;Hughes et al, 2007;Mallory et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Our data shows that changes in posttranslational modification of PGRMC1 result in altered metabolism, genomic mutation rates, and epigenetic methylation status. Future research should examine whether genomic effects involve previously reported PGRMC1 involvement with G0/G1 checkpoint and/or spindle association [2,[20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Some functions evidently arose in eukaryotes (e.g. membrane trafficking (reviewed by: [2,19]), cell cycle regulation at the G0/G1 checkpoint [2,20,21], mitotic/meiotic spindle association [22][23][24]). Other clearly specialized metazoan functions include e.g., hormonal influence on fertility, embryogenic axon guidance, and membrane trafficking associated with synaptic plasticity [reviewed by : 2, 25].…”
Section: Introductionmentioning
confidence: 99%